2020
DOI: 10.21203/rs.3.rs-28779/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Corticosteroids on the Respiratory Microbiome: A Systematic Review

Abstract: Background: Since its discovery, the respiratory microbiome has been implicated in the pathogenesis of multiple pulmonary diseases. Even though corticosteroid treatments are widely prescribed for pulmonary diseases, their effects on the respiratory microbiome are still poorly understood. This systematic review summarises the current understanding of the effects of corticosteroids on the microbiome of the airways. The primary outcomes of interest were changes in the diversity, composition and total burden of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Importantly, within asthmatic subjects we did not find current ICS use to be associated with additional microbial abnormalities. The presence or absence of ICS induced changes in the bacterial microbiota is contentious [58] , but our results are consistent with controlled studies of steroid and antibiotic naïve wheezing infants [59] and adults with steroid-naive atopic asthma [60] . We were not able to inform on ICS effects in the thoracic airways or in more severe disease.…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, within asthmatic subjects we did not find current ICS use to be associated with additional microbial abnormalities. The presence or absence of ICS induced changes in the bacterial microbiota is contentious [58] , but our results are consistent with controlled studies of steroid and antibiotic naïve wheezing infants [59] and adults with steroid-naive atopic asthma [60] . We were not able to inform on ICS effects in the thoracic airways or in more severe disease.…”
Section: Discussionsupporting
confidence: 89%
“…Hartmann et al performed a systematic review and reported that corticosteroids may have an important effect on the composition of the respiratory microbiome, but there was no clear shared direction as a result of the heterogeneous nature of the methods used and the populations investigated. 15 The effect of ICS on the microbiome, especially mycobiome and bacterial-fungal, fungal-fungal, and bacterial-bacterial networks, remains to be elucidated. In this study we aimed to investigate the effect of ICS on the airway microbiome and microbial connections in asthma patients over a 9-month period.…”
Section: Introductionmentioning
confidence: 99%
“…Different inhaled ICS showed different effects on the lung microbiome, although different inhaled ICS may have similar effects on the phagocytic function of macrophages in animal experiments. Hartmann et al performed a systematic review and reported that corticosteroids may have an important effect on the composition of the respiratory microbiome, but there was no clear shared direction as a result of the heterogeneous nature of the methods used and the populations investigated 15 . The effect of ICS on the microbiome, especially mycobiome and bacterial–fungal, fungal–fungal, and bacterial–bacterial networks, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…We thank PD Dr. Christian Appenzeller-Herzog of the University of Basel for significant contributions in the planning and early execution stages of this systematic review. This manuscript has been released as a pre-print at Research Square ( 45 ).…”
mentioning
confidence: 99%